Relationship Between Growth, Profitability And Stock Returns Amongst The Non-Financial Companies Listed On FTSE Bursa Malaysia KLCI - Soon, Yu Shen (2021)
Based on the Signaling Theory, strong financial performance exhibited by public-listed Companies will convey positive signals about the companies’ future financial performance. Investors would respond to the positive signals by increasing the demand for the companies’ Stocks, which in turn drives up the stock prices of those companies. This study has Examined whether stock returns would respond to signals conveyed by revenue growth, Earnings growth, and changes in profitability. The sample involved in this study amounted To 22 non-financial companies listed on the FTSE Bursa Malaysia KLCI from 2013 to 2019. The panel data regressions were used to analyse the relationship between stock returns, Revenue growth, earnings growth, and changes in profitability. The results indicated that Only earnings growth convey meaningful signals that influence stock returns. On the other Hand, revenue growth and changes in profitability are unable explain the variation in stock Returns amongst the non-financial companies listed on the FTSE Bursa Malaysia KLCI